Risk Factor for Musculoskeletal Disorder in Construction Worker: Literature Review - Arif Rahmat Abdullah; Indri Hapsari Susilowati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Musculoskeletal Disorders (MSDS) is a condition involving degenerative health problems or inflammation that occurs in workers, affecting joints, ligaments, muscles, tendons and blood vessels. Sufferers of muscle and skeletal disorders as an occupational disease are the largest number of cases of occupational disease in Europe compared to other diseases in 2017. Objective: This research aims to identify factors Risk factors for muscle and skeletal disorders in construction workers. Method: This research uses the method literature study using the PRISMA approach (preferred reporting items for systematic reviews and meta-analyses). When searching for journals that are relevant to the research topic, use a search engine Science Direct and ResearchGate using the keyword "Musculoskeletal Disorder” and” Construction Worker”. A total of 868 journals were identified, but 8 journals met the inclusion and exclusion criteria. Result: Research instruments used Standard Nordic Musculoskeletal Questionnaire. It was found that construction workers generally experience pain in the legs, followed by pain in the back, head, hips, shoulders and other areas. The pain felt by workers is caused by behavioral factors (lifestyle, smoking behavior), place and work environment factors (work position, vibration and temperature, work experience, workload, wage system), worker psychological factors (level of fatigue after work, Job stress), Individual Factors (BMI, Exercise, Work experience, Age). Conclusion: Risk factors for muscle and skeletal disorders in construction workers consist of behavioral factors, place and work environment factors, worker psychological factors, and individual factors.